Silver recovery from flotation tailings, by acid-chlorine leaching - Aramburú Rojas, Vidal Sixto (2000)
The interest of recovering the flotation tailings containing silver , there has been many years ago, mainly by large volumes and significant silver tenors these metals involved. Metallurgical studies to find a suitable treatment scheme for these tailings have been conducted , evaluating alternatives pyro and hydrometallurgical laboratory level. As a conclusion of this work, the hydrometallurgical process of acid leaching was selected - chlorinating, for best metal performance and flexibility. This paper mainly covers the results obtained at the laboratory, where the main variables of the process are evaluated. Such as particle size , concentration and pH of the leaching . The results at the laboratory showed that NaCl solutions acidified with 25% sulfuric acid, it is possible to extract about 40 % of the silver content, value would be limited by the mineralogical composition of the tailings complex, because silver is finely disseminated pyrite and possibly due to the presence of insoluble secondary compounds (jarosite argento). The elements present in the leach solutions, such as Ag , Cu, are recovered by cementation process with scrap iron, yielding precipitates whose composition varies between 2 to 6% Ag, 10-30 % Cu . This product can be integrated easily into the circuitry of the casting treatments.